2007
DOI: 10.1086/524125
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Slotting Contracts

Abstract: Slotting fees, per-unit-time payments made by manufacturers to retailers for shelf space, have become increasingly prevalent in grocery retailing. Shelf space contracts are shown to be a consequence of the normal competitive process when retailer shelf space is promotional, in the sense that the shelf space induces profitable incremental individual manufacturer sales without drawing customers from competing stores. In these circumstances, retailer and manufacturer incentives do not coincide with regard to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 19 publications
1
52
0
1
Order By: Relevance
“…These results can be proved by di¤erentiating (13) and (14) with respect to n and taking into account ; 2 (0; 1) as well as n 1.…”
Section: Short-term Contractsmentioning
confidence: 90%
See 2 more Smart Citations
“…These results can be proved by di¤erentiating (13) and (14) with respect to n and taking into account ; 2 (0; 1) as well as n 1.…”
Section: Short-term Contractsmentioning
confidence: 90%
“…The analysis is further simpli…ed by the assumption of no renegotiations if n = N holds. 8 Starting with the case n = N , where outside suppliers are lacking for immediate replacement in the case of negotiation breakdown, the upfront payment G i of supplier i is determined by (see (13) and (14)):…”
Section: Long-term Contractsmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to supermarkets, Wal-Mart does not have any slotting fees or hidden allowances (Walton, 2005); instead it receives lower wholesale price as a compensation for shelf space (Klein and Wright, 2007 …”
Section: Reasonable Discount Rate For Wal-martmentioning
confidence: 99%
“…In the years following Telser's contribution, several scholars have shown that RPM and other vertical restraints can be used to enhance dealers' incentives beyond the realm of point-of-sale service provision, including the incentive to promote product quality, ensure promotional efforts, engage in proper rotation of perishable goods, etc. (see, e.g., Klein and Murphy, 1988;Klein and Wright, 2007;Wright, 2007).…”
mentioning
confidence: 99%